2016
DOI: 10.1556/650.2016.30456
|View full text |Cite
|
Sign up to set email alerts
|

Az internet hatása az orvos–beteg viszonyra

Abstract: Az internet kikerülhetetlen tényezővé vált az egészségügyben és az orvos-beteg kapcsolatban. Hatását két elméleti keretben érdemes vizsgálni: az orvosi hivatásra gyakorolt hatás mellett a döntéshozatali mechanizmusokkal való köl csönhatás elemzése segít értelmezni a jelenséget, hogy a páciensek az interneten informálódnak betegségükről, a le hetséges gyógymódról vagy az orvosról. Az orvosok többsége idegenkedik attól, hogy a páciensek az internetet is felhasználják gyógyulásuk érdekében, és aggályaikban nem cs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 22 publications
1
8
0
1
Order By: Relevance
“…Many Internet users have switched to the Internet to obtain information about health and health care [2,3]. The Internet World Stats report indicates that the number of Internet users in Egypt has increased from 29.8 million in June 2015 (32.6% of the population) to 33.3 million in June 2016 (37.0% of the population) [4].…”
Section: Introductionmentioning
confidence: 99%
“…Many Internet users have switched to the Internet to obtain information about health and health care [2,3]. The Internet World Stats report indicates that the number of Internet users in Egypt has increased from 29.8 million in June 2015 (32.6% of the population) to 33.3 million in June 2016 (37.0% of the population) [4].…”
Section: Introductionmentioning
confidence: 99%
“…In agreement with previous studies, we observed that instant messaging services are an alternative way for physicians to communicate with patients or their families, and that these services present several advantages. [24][25][26] The perceived benefits that have been observed within medical practice include reduction of medical errors 31 due to rapid online consultation and information sharing; strengthening of physician-patient relationships, related to creation of "dedicated conversation channels"; democratization of medical management, 21,22 since team-based decision-making can be implemented and patients' preferences can also be considered; and most importantly, increased access to healthcare services, through reaching out to remote and socially vulnerable populations. 23 In a Malaysian study, it was perceived that use of mobile messaging apps had a positive effect regarding coronary artery disease patients' knowledge of and adherence to a healthy lifestyle.…”
Section: Discussionmentioning
confidence: 99%
“…After reading the abstracts of these review papers, we found that scholars in other geographical areas mainly focused on online health information seeking [37,38,39,40,41], social media use in healthcare [42], Internet-based interventions (IPIs) [43], online community [44,45], and e-health [46]. Compared to our results, scholars in other areas mainly focused on online health information seeking and Internet-based interventions.…”
Section: Discussionmentioning
confidence: 99%